الحكمة في تشريع الزواج: الحوار مع أنصار اللبرالية في تحريم زواج المسلمة بغير المسلم - Harda Armayanto (Universitas Darussalam Gontor, 2017)
This article discusses the prohibition of interfaith marriage or “mixed marriage” between Muslimah and non-Muslim. According to the proponent of religious liberalism, there is no prohibition in Islam related to this kind of marrige. They argue that there is no clear and unambiguous prohibition in the Islamic scriptures about it. The prohibition is only coming from Muslim jurists (fuqahâ). Meanwhile, the prohibition of mixed marriage between Muslimah and non-Muslim in the era of the Prophet (PBUH) due to political conditions at that time, where the number of Muslims was still small, and so it was feared to have an impact on the decline in their quantity. In fact, Islam required a large number of adherents at its beginning. On that basis, the authors review the verses of the Koran, the hadith of the Prophet (PBUH), and the books of turâth in order to get the right answer related to this problem. Through the study of wisdom of the marriage legislation, it is known why Islam prohibited this type of marriage. The marriage legislation in Islam is not only to get descendant, but also to keep religion. It is clear, the Qur’an said that the main reason for the prohibition of this marriage is because Muslimah will fall into kufr. It is undeniable that a wife must submit and obey her husband. How can a Muslimah obey her husband, if the husband invites him to kufr? Surely this is a paradox.